Circadian rhythm effect on physical tennis performance in trained male players - Lopez-Samanes, A.; Moreno-Pérez, D.; Maté-Muñoz, J. L.; Dominguez, R.; Pallarés, J. G.; Mora-Rodriguez, R.; Ortega, J. F. (Journal of Sports Sciences, 2017)
To determine the effect of circadian rhythm on neuromuscular responses and kinematics related to physical tennis performance, after a standardised warm-up, 13 highly competitive male tennis players were tested twice for serve velocity/accuracy (SVA), countermovement vertical jump (CMJ), isometric handgrip strength (IS), agility T-test (AGIL) and a 10-m sprint (10-m RUN). In a randomised, counter-balance order, tennis players underwent the test battery twice, either in the morning (i.e., AM; 9:00 h) and in the afternoon (i.e., PM; 16:30 h). Paired t-tests were used to analyse differences due to time-of-day in performance variables. Comparison of morning versus afternoon testing revealed that SVA (168.5 ± 6.5 vs. 175.2 ± 6.1 km · h-1; P = 0.003; effect size [ES] = 1.07), CMJ (32.2 ± 0.9 vs. 33.7 ± 1.1 cm; P = 0.018; ES = 1.46), AGIL (10.14 ± 0.1 vs. 9.91 ± 0.2 s; P = 0.007; ES = 1.23) and 10-m RUN time (1.74 ± 0.1 vs. 1.69 ± 0.1 s; P = 0.021; ES = 0.67) were significantly blunted during the morning testing. However, IS was not affected by time-of-day (P = 0.891). Thus, tennis performance may be reduced when competing in the morning in comparison to early evening. Therefore, coaches and tennis players should focus on schedule the SVA, power, speed and agility training sessions in the afternoon.